N-type organic thermoelectrics: demonstration of ZT > 0.3 - Liu, Jian; van der Zee, Bas; Alessandri, Riccardo; Sami, Selim; Dong, Jingjin; Nugraha, Mohamad I.; Barker, Alex J.; Rousseva, Sylvia; Qiu, Li; Qiu, Xinkai; Klasen, Nathalie; Chiechi, Ryan C.; et al. (Nature communications, 2020)
The ‘phonon-glass electron-crystal’ concept has triggered most of the progress that has been achieved in inorganic thermoelectrics in the past two decades. Organic thermoelectric materials, unlike their inorganic counterparts, exhibit molecular diversity, flexible mechanical properties and easy fabrication, and are mostly ‘phonon glasses’. However, the thermoelectric performances of these organic materials are largely limited by low molecular order and they are therefore far from being ‘electron crystals’. Here, we report a molecularly n-doped fullerene derivative with meticulous design of the side chain that approaches an organic ‘PGEC’ thermoelectric material. This thermoelectric material exhibits an excellent electrical conductivity of >10 S cm −1 and an ultralow thermal conductivity of <0.1 Wm −1 K −1 , leading to the best figure of merit ZT = 0.34 (at 120 °C) among all reported single-host n-type organic thermoelectric materials. The key factor to achieving the record performance is to use ‘arm-shaped’ double-triethylene-glycol-type side chains, which not only offer excellent doping efficiency (~60%) but also induce a disorder-to-order transition upon thermal annealing. This study illustrates the vast potential of organic semiconductors as thermoelectric materials. Achieved high thermoelectric figure of merit (ZT) in organic thermoelectric materials remains a challenge due to their low packing order and poor host/dopant miscibility. Here, the authors report side chain-engineered n-doped fullerene derivatives with record ZT >0.3 for organic thermoelectrics.